Politics of memory : the Israeli Underground's struggle for inclusion in the national pantheon and military commemoralization - Lebel, Udi.; Arens, Moshe; Kadishai, Yehiel (New York : Routledge, 2013)
"The production and management of public memory in Israel has been politicized through the efforts of successive Israeli governments. In the nascent years of the Israeli state, the ruling Labour Party sought to influence the collective memory of the people through selective production and collective assimilation of cultural practices associated with bereavement and commemoration. In tandem, efforts were made to fashion a ranking order of heroism and sacrifice through various means of memorialisation. Politics of Memory focuses on the struggle for inclusion in the domain of military commemoration by those barred from its patrimony and examines the effect of this struggle for the Israeli governments' legitimacy. A thought provoking study of the inclusion and exclusion processes of military commemoralization, and the effects of this for Israeli national identity, this book will be of interest to students and scholars of Israeli history, military studies and politics in general"--
pt. 1. Theoretical and historical framework -- pt. 2. The exclusion from national pantheon -- pt. 3. Penetrating the gates of national pantheon and collective memory -- pt. 4. Politics of memory and the changing boundaries of national pantheon.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Memory; Memorials -- Israel; Bereavement -- Israel; Electronic books